Quantitative Classification of Desertification Severity for Degraded Aquifer Based on Remotely Sensed Drought Assessment - Pantelis Sidiropoulos; Nicolas R. Dalezios; Athanasios Loukas; Nikitas Mylopoulos; Marios Spiliotopoulos; Ioannis N. Faraslis; Nikos Alpanakis; Stavros Sakellariou (Hydrology, 2021)
Natural and anthropogenic causes jointly lead to land degradation and eventually to desertification, which occurs in arid, semiarid, and dry subhumid areas. Furthermore, extended drought periods may cause soil exposure and erosion, land degradation and, finally, desertification. Several climatic, geological, hydrological, physiographic, biological, as well as human factors contribute to desertification. This paper presents a methodological procedure for the quantitative classification of desertification severity over a watershed with degraded groundwater resources. It starts with drought assessment using Standardized Precipitation Index (SPI), based on gridded satellite-based precipitation data (taken from the CHIRPS database), then erosion potential is assessed through modeling. The groundwater levels are estimated with the use of a simulation model and the groundwater quality components of desertification, based on scattered data, are interpolated with the use of geostatistical tools. Finally, the combination of the desertification severity components leads to the final mapping of desertification severity classification.